2008
DOI: 10.4314/ajid.v2i1.42090
|View full text |Cite
|
Sign up to set email alerts
|

Family Communication On HIV/AIDS Among Secondary School Students In A Northern State Of Nigeria

Abstract: Most Adolescents in Nigeria, like many others in Africa, are potentially at risk for contracting HIV through unprotected sexual intercourse. Yet the issue of how to help youth avoid risky sexual behaviour through family communication / education on HIV/AIDS is still of serious arguments within the society. This study examines the practice of family communication on HIV / AIDS among secondary school students. A descriptive study using 420 secondary school students selected by multi-stage random sampling was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 10 publications
8
16
2
2
Order By: Relevance
“…This is in contrast to a study in Nigeria in which 98% of students reported discussion about condoms with a 'family member' [35]. This study also found that 34% of respondents reported discussion about premarital sex with a family member.…”
Section: Resultscontrasting
confidence: 99%
“…This is in contrast to a study in Nigeria in which 98% of students reported discussion about condoms with a 'family member' [35]. This study also found that 34% of respondents reported discussion about premarital sex with a family member.…”
Section: Resultscontrasting
confidence: 99%
“…This was attributed to a number of reasons such as parental fears concerning potential side effects such as infertility, that it would contradict their intended message emphasizing abstinence and due to shyness and lack of knowledge. This is in contrast to a study in Nigeria in which 98% of students reported discussion about condoms with a 'family member' (Musa, Akande, Salaudeen & Soladoye, 2008). This study also found that 34% of respondents reported discussion about premarital sex with a family member.…”
Section: Frequency and Content Of Discussioncontrasting
confidence: 99%
“…A total of 20 of 23 studies investigated frequency of discussion about a range of topics related to HIV/AIDS and sexuality between caregivers or parents and children. Firstly, in relation to HIV/AIDS, studies relying on data collected from young people reported proportions in assessing frequency of communication about HIV/AIDS with parents ranging from 8% to 80%, while other studies reported mean values (Namisi et al, 2009;Kawia et al, 2008;Musa, Akande, Salaudeen & Soladoye, 2008;Mathew, Shugaba & Ogala, 2006;Bastien, Sango, Mnyika, Masatu & Klepp, 2008;Bastien, Leshabari & Klepp, 2009;Babalola, Tambashe & Vondresek, 2005;Poulsen et al, 2010;Biddlecom, Awasabo-Asare & Akinrinola, 2009). One study looked at change over time from 1992 to 2005 in the same randomly selected primary schools in two regions in Tanzania in talking about AIDS with parents (Bastien, Sango, Mnyika, Masatu & Klepp, 2008).…”
Section: Frequency and Content Of Discussionmentioning
confidence: 99%
“…It has been observed that most youths become sexually active before marriage whilst still in their teens. Most adolescents and especially secondary school students in Nigeria are potentially at risk of contracting HIV through unprotected sexual intercourse (Musa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that about 50% of unmarried teenagers, aged 15 -19 years had begun sexual activity without proper protection (Musa et al, 2008). There are many religious and cultural ways which had helped to change sexual behaviors positively and which had helped to eliminate further spread of HIV.…”
Section: Introductionmentioning
confidence: 99%